PERSEPSI GURU SMK TERHADAP PENERAPAN KECERDASAN BUATAN DALAM PEMBELAJARAN INFORMATIKA - Indra Jati Desrizal; Ta'ali; Titi Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of artificial intelligence (AI) continues to reshape learning practices, including Informatics subjects in vocational high schools, where teachers are required to be increasingly adaptive to modern technologies. However, the level of AI utilization in vocational education remains varied and is strongly influenced by teachers’ perceptions as the key actors in classroom implementation. This study aims to analyze vocational school teachers’ perceptions of AI integration in Informatics learning, focusing on perceived usefulness, ease of use, readiness, and the challenges they encounter. The research employed a quantitative descriptive survey method involving Informatics teachers from several vocational schools. Data were collected using a validated Likert-scale questionnaire,and analyzed with descriptive statistics. The findings indicate that most teachers hold positive perceptions of AI, recognizing its potential to support material preparation, assessment processes, and personalized learning. Nevertheless, actual implementation remains limited due to constraints such as insufficient technical skills, lack of structured training, and inadequate school facilities and connectivity. These results highlight the need to strengthen teachers’ literacy and competencies through practice-oriented training and the provision of supporting infrastructure to ensure effective AI integration in Informatics learning.